CIVIL COMPETENCE AS AN IMPORTANT COMPONENT OF THE PROFESSIONAL GROWTH OF A MODERN TEACHER - Савченко, Світлана; Олексенко, Світлана (SWorldJournal, 2023)
The formation of civic competence of teachers is an integral part of their professional and personal development, an important condition for the formation of a civil society. The article examines the possibilities of the post-graduate education and adult